ANALISIS FAKTOR-FAKTOR MOTIVASI KERJA PEGAWAI PADA DINAS KEPENDUDUKAN DAN CATATAN SIPIL (DUKCAPIL) KABUPATEN SAROLANGUN - - Dahmiri; - Lismawati (Universitas Trunojoyo Madura, 2015)
This study, entitled Analysis of Factors Employee Motivation at the Department of Population and Civil Sarolangun. The purpose of this study was to determine and analyze the motivational factors of employees working in the Department of Population and Civil Registration Sarolangun.The method used in this peniliaan is a qualitative descriptive method, which is an existing fact or fenome field and then analyzed by the relevant theories and concepts and variables measured with Likert scale. The study sample as many as 45 people. The collection of data by distributing questionnaires. The data is processed by using a range of scales.Based on the results of the study, known Motivation Employees at the Department of Population and Civil Registration Sarolangun average scores on the indicators of employee motivation in the Department of Population and Civil Registration Sarolangun number of scores obtained amounted to 1,149, or an average of 164.1, which means entering into good motivation category.